Situation Report: Bulgaria, 2 December 1968 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Zhivkov on Socialist Democracy Bulgarian Policy in the Balkans Bulgarian Writers Open Ideological Conference National Conference of Inventors Ended Miscellaneous Trade Agreement with UAR Bulgarian-Cuban Economic Contacts Trade Delegation in Poland Cultural Agreement with Japan Talks on Tourist Exchange with Czechoslovakia